Kecemasan Orang Tua yang Memiliki Anak Disabilitas Intelektual di SLBN 4 Jakarta - gidion, hermito; Sitorus, Purnama Betty; Humayrah, Zahrah nabila (UI Scholars Hub, 2025)
Anxiety is a common mental condition characterized by feelings of nervousness, fear, and restlessness that can interfere with daily life. Parents who have children with intellectual disabilities often experience anxiety due to various factors, including psychological pressure and high emotional burdens. The aim of this study was to analyze the level of anxiety among parents who have children with intellectual disabilities at SLBN 4 Jakarta and to identify the relationship between predisposing and precipitating factors and the level of anxiety. This research employed a quantitative descriptive approach with a cross-sectional design. The sample consisted of 81 parents at SLBN 4 Jakarta. Data were collected using a researcher-developed questionnaire to assess predisposing and precipitating factors, and the Hamilton Anxiety Rating Scale (HARS) to measure anxiety levels. The results showed that the majority of parents had mild anxiety levels (46.9%), while 40.7% did not experience anxiety. Spearman correlation analysis revealed no significant relationship between predisposing factors (r = 0.002; p = 0.988) or precipitating factors (r = 0.060; p = 0.593) and parental anxiety levels. However, there was a significant relationship between marital status and anxiety levels (p = 0.000). This study concludes that genetic and precipitating factors, such as medical conditions or exposure to certain substances, had little influence on parental anxiety in this context, although emotional vulnerability showed the highest average score. The implications of this study highlight the importance of social support and tailored interventions for parents.